A tale of two syn-rifts: New age information and depositional environment interpretation for the North Falkland Basin syn-rift and implications for the rifting of Gondwana - Rory J. Sutton; Gayle E. Plenderleith; Thomas J.H. Dodd; Lorraine P. Field; Ian L. Millar; Dave J. McCarthy; Thomas A. Randles (Gondwana Research, 2026)

The pulse of continental crust production and the structure of the galaxy - C.L. Kirkland; M. Brown; P. Sutton; T.E. Johnson (Earth and Planetary Science Letters, 2026)

Deep intact proteoform quantification of low-microgram-scale proteome by tandem mass tag labeling and online 2D high-pH/low-pH RPLC top-down analysis - Yanting Guo; Trishika Chowdhury; Walter P. Galie; Kellye A. Cupp-Sutton; Zhitao Zhao; Ashlyn Solenberger; Dahang Yu; Si Wu (Analytica Chimica Acta, 2026)

G protein signaling capabilities at the bradykinin 2 receptor - Shradha V. Darira; Laurie P. Sutton (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
The bradykinin 2 receptor (B2R) is one of two members of the kinin receptor family and is a G protein–coupled receptor (GPCR) that regulates important physiological processes including pain, inflammation, and cardiovascular homeostasis. Functionally, B2R is activated by the kinin peptides, bradykinin and kallidin. Carboxypeptidase cleavage of bradykinin and kallidin results in the formation of des-Arg9-bradykinin (DABK) and des-Arg10-kallidin (DAKD) respectively, which are classically described as agonists of the bradykinin 1 receptor (B1R), the other member of the kinin family. Affinity binding studies have reported that DABK and DAKD can also bind to B2R. Upon activation, B2R signals through the recruitment of heterotrimeric G proteins, and earlier work has highlighted the promiscuous G protein coupling to B2R in response to bradykinin. However, a comprehensive G protein activation profile of the B2R receptor when activated by the other endogenous agonists has not yet been established. In this study, we used Bioluminescence Resonance Energy Transfer (BRET)–based in vitro assays to monitor the coupling of 14 different Gα proteins upon B2R activation. Our results show that there is a shift in G protein activation profiles and kinetics among the different peptides. By analyzing responses across a range of agonist concentrations, we further identified biased signaling among these peptides, with differential activation of specific Gα subtypes. These results improve understanding of intracellular mechanisms through which the kinin system regulates different aspects of its physiological role and provide valuable information for the design of drugs targeting the kinin receptors.

Chitosan-based antimicrobial filter media for point-of-use water treatment: a proof-of-concept study - Liping Pang; Aden Sadler; Micki Bell; Sophie Harris; Erin McGill; Richard Sutton; Glenn Rowland; Mark P. Staiger (Environmental Science and Pollution Research, 2026)

Infill density mediates human oral breakdown and nutrient digestion kinetics of 3D-printed wheat-pea protein foods - Chengyi Yang; Sze Ying Leong; Jessie King; Esther H.-J. Kim; Marco P. Morgenstern; Mei Peng; Kevin Sutton; Indrawati Oey (Food Structure, 2026)

Deep Dark Futures: Foresighting Human Impacts on Mesopelagic Ecosystem Services - Ben Scoulding; Alistair J. Hobday; Rowan Trebilco; Heidi Pethybridge; Ingrid van Putten; Katherine Baker; Karen Evans; David Green; Eriko Hoshino; Haris Kunnath; Clothilde Langlais; Tim P. Lynch; et al. (Fish and Fisheries, 2026)
Most of the global mesopelagic zone lies beyond the jurisdiction of any single government or entity, making equitable access and sustainable management for ecosystem services (ES) difficult. Here, a foresighting approach was used to examine the plausible consequences of four speculative scenarios of human activity on the mesopelagic zone and its associated ES. Large‐scale Harvest represented the provisioning ES, with concerns over unsustainable removal of mesopelagic biota. Climate Mitigation, a regulating ES, involved harvesting and then dumping mesopelagic biota to maximise carbon drawdown. In Geopolitical Manoeuvring, the scenario focused on cultural ES; mesopelagic fisheries were used as a geopolitical instrument to assert claims over ocean spaces. Finally, Mineral Extraction, a supporting ES, considered the impact of deep‐sea mining on mesopelagic ecosystems. Drivers and indicators for each scenario were identified, and qualitative network models were created to assess impact on the different system components using press perturbations. Model outputs highlighted the central role that mesopelagic biota play in supporting and regulating other ecosystem components and the likely negative impacts of reduced biomass on higher order predators and ocean carbon storage. Interestingly, biological indicators performed poorly as early warning signals of change across all scenarios; instead, the most effective indicators were related to science and technology, economics and governance. International agreements for sustainable use of the mesopelagic zone are needed to avoid loss of ES underpinning all scenarios. While this foresighting focused on the mesopelagic zone, the approach of developing scenarios, models and indicators has broader applicability to studies of other systems.

Past trajectory of a Northwest Europe socio-ecosystem at the land-sea interface: Case study of the northern watersheds of the Bay of Brest over the last 150 years - C. Valero; A. Penaud; M. Vidal; E. Goubert; P.A. Dessandier; S. Schmidt; E. Glémarec; P. Brigode; L. Bosseboeuf; Y.M. Paulet; J. Sutton; P. Ailliot; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Uncovering redox-specific biotransformation of organic micropollutants - Alessia Ore; Rick Helmus; Annemarie P. van Wezel; Nora B. Sutton (Journal of Hazardous Materials, 2026)

GOOS Essential Ocean Variables: the backbone of a sustained and evolving global ocean observing system - Belén Martín Míguez; Emma Heslop; Narissa Bax; Lisandro Benedetti-Cecchi; Gabrielle Canonico; Kim Currie; Karen Evans; Albert S. Fischer; Véronique Garçon; Maria Hood; Johannes Karstensen; Ana Lara-López; et al. (Frontiers in Marine Science, 2026)
The need for ocean information has never been greater. From climate change to food security and extreme events, we need to understand the role of the ocean and better predict change and impact. This is only possible with the sustained collection of a key set of ocean observations. The Global Ocean Observing System (GOOS) coordinates international efforts to collect these Essential Ocean Variables (EOVs), which span physics, biogeochemistry, biology and ecosystem realms. Guided by three expert panels, these EOVs are used to define the needs and design of a sustained, fit for purpose global ocean observing system, aimed at maximizing investments in observing infrastructure. As the GOOS EOVs are increasingly used, it has become important to discuss and refine the understanding of this framework, to ensure that the right balance is struck between their essential nature and the need to expand to new domains and integrate with key global policies. In this paper we provide a description of the EOV framework, discuss some of the challenges in implementing it, and identify a set of recommendations for GOOS and the ocean observing community to take forward. These recommendations include increasing the transparency of the EOV adoption process, and the need to periodically assess the EOVs in consultation with observing communities and with the entities managing other global essential variable frameworks in cross cutting realms such as climate and biodiversity. This will contribute to building a useful and responsive global ocean observing system that delivers the observations required to meet societal needs.

Higher microbial diversity enhances the extent and rate of organic micropollutant biodegradation under aerobic and nitrate-reducing conditions - Alessia Ore; Emma H. Palm; Annemarie P. van Wezel; Nora B. Sutton (Water Research, 2026)

Removal, transport, and transformation of organic micropollutants in managed aquifer recharge: Insights from target and non-target analyses - Alessia Ore; Gabriel Sigmund; Jan Specker; Rick Helmus; Patricia Aguilar-Alarcón; Merijn Schriks; Annemarie P. van Wezel; Nora B. Sutton (Water Research, 2025)

Modulating oral breakdown and digestibility of wheat pasta through pea protein incorporation - Chengyi Yang; Sze Ying Leong; Jessie King; Esther H.-J. Kim; Mei Peng; Dominic Agyei; Marco P. Morgenstern; Kevin Sutton; Indrawati Oey (Food Research International, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Aotearoa New Zealand’s marine carbon cycle in a changing climate – Current understanding and future directions - Scott D. Nodder; Cliff S. Law; Erik Behrens; Sarah J. Bury; Antonia Cristi; Charine Collins; Kim I. Currie; Moira Décima; Alain De Verneil; Pablo C. Escobar‐Flores; Denise Fernandez; Mark P. Gall; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
The marine system plays a critical role in the global climate cycle, as a major control of atmospheric carbon dioxide (CO 2 ). Marine primary production (photosynthesis) and remineralisation of organic carbon (respiration, degradation) determine the amount of CO 2 sequestered in marine sediments and deep‐water environments on century to millennial timescales. The stocks and fluxes of the marine carbon cycle are susceptible to global climate change impacts and other anthropogenic activities that modify key processes. Oceanographic studies of the marine carbon cycle in Aotearoa New Zealand’s Exclusive Economic Zone (NZ EEZ) and Territorial Seas over past decades have provided broad knowledge across a complex and dynamic seascape, but there remain fundamental knowledge gaps that limit identification of and response to present and future anthropogenic threats. In particular, several areas of the EEZ have been under‐sampled and there are currently insufficient data to establish baselines and variability for the marine carbon cycle. We recommend that new observational technologies and ocean modelling applications be fully developed and utilised to enable development of robust predictive capability of our ocean’s response to human‐induced perturbations. Future focus on oceanic nature‐based solutions to accelerate CO 2 uptake will require improved knowledge of the marine carbon cycle in NZ’s EEZ.

Ultrasensitive Staphylococcal Enterotoxin B Quantum Dot-Based Lateral Flow Immunoassays for Rapid Testing of Poultry Rinsates and Milk - Lance P. Ford; Skyler B. Sutton; Daniel R. Mitchell; John G. Bruno (Journal of Fluorescence, 2025)

Incorporating buccal mass planar mechanics and anatomical features improves neuromechanical modeling of Aplysia feeding behavior - Michael J. Bennington; Ashlee S. Liao; Ravesh Sukhnandan; Bidisha Kundu; Stephen M. Rogers; Jeffrey P. Gill; Jeffrey M. McManus; Gregory P. Sutton; Hillel J. Chiel; Victoria A. Webster-Wood (Biological Cybernetics, 2025)
To understand how behaviors arise in animals, it is necessary to investigate both the neural circuits and the biomechanics of the periphery. A tractable model system for studying multifunctional control is the feeding apparatus of the marine mollusk Aplysia californica . Previous in silico and in roboto models have investigated how the nervous and muscular systems interact in this system. However, these models are still limited in their ability to match in vivo data both qualitatively and quantitatively. We introduce a new neuromechanical model of Aplysia feeding that combines a modified version of a previously developed neural model with a novel biomechanical model that better reflects the anatomy and kinematics of Aplysia feeding. The model was calibrated using a combination of previously measured biomechanical parameters and hand-tuning to behavioral data. Using this model, simulated feeding experiments were conducted, and the resulting behavioral metrics were compared to animal data. The model successfully produces three key behaviors seen in Aplysia and demonstrates a good quantitative agreement with biting and swallowing behaviors. Additional work is needed to match rejection behavior quantitatively and to reflect qualitative observations related to the relative contributions of two key muscles, the hinge and I3. Future improvements will focus on incorporating the effects of deformable 3D structures in the simulated buccal mass.

Organocatalytic glycolysis of polyethylene terephthalate and product separation by membrane filtration - Joseph Sutton; Guido Grause; Ali Al Rida Hmayed; Steven T.G. Street; Andrew P. Dove; Joseph Wood (Chemical Engineering Journal, 2025)

Seasonality and hydroclimatic variability shape the functional and taxonomic diversity of nearshore fish communities in glacierized estuaries of Alaska - Lauren Sutton; Brian P. Ulaski; Nina C. Lundstrom; Emily J. Whitney; Jason B. Fellman; Anne H. Beaudreau; Jordan Jenckes; Scott S. Gabara; Brenda Konar (Journal of Experimental Marine Biology and Ecology, 2025)

Mesopelagic Fish Traits: Functions and Trade‐Offs - Henrike Andresen; Leandro Nolé Eduardo; M. Pilar Olivar; P. Daniël van Denderen; Jérôme Spitz; Aurore A. Maureaud; Anik Brind'Amour; Noelle M. Bowlin; Eva García‐Seoane; Tom J. Langbehn; Tracey T. Sutton; Heino O. Fock; et al. (Fish and Fisheries, 2025)
Fishes inhabiting the mesopelagic zone of the world's oceans are estimated to account for the majority of the world's fish biomass. They have recently attracted new attention because they are part of the biological carbon pump and have been reconsidered as a contribution to food security. Hence, there is an urgent need to understand how environmental conditions and species interactions shape their assemblages, and how they contribute to the functioning of marine ecosystems. Trait‐based approaches are valuable for addressing these types of questions. However, the biology and ecology of mesopelagic fishes are understudied compared to fishes in shallow and epipelagic waters. Here, we synthesise existing knowledge of traits of mesopelagic fishes and relate them to their role in survival, feeding and growth and reproduction, the key functions that contribute to fitness. Vertical migrations, specialised vision and the use of bioluminescence are among the most striking adaptations to the conditions in the mesopelagic realm. Many traits are interrelated as a result of trade‐offs, which may help to understand selection pressures. While morphological traits are straightforward to observe, major knowledge gaps exist for traits that require frequent sampling, assessment under experimental conditions or age determination. The unique adaptations of mesopelagic fishes need to be included in management strategies as well as fundamental research of the habitat.

Life in the margins: the effect of immersion/emersion and tidal cycle on the North Atlantic limpet Patella vulgata protein synthesis rates - Ignacio A. Cienfuegos; Benjamin J. Ciotti; Richard A. Billington; Paul A. Sutton; Simon G. Lamarre; Keiron P. P. Fraser (Journal of Comparative Physiology B, 2024)

Letter to the editors regarding “Inter-laboratory validation of bioaccessibility testing for metals” by Henderson et al. (2014) - P.E. Rasmussen; P. Huntsman; T.M. Singer; M.N. Jacobs; C.C. Trevithick-Sutton (Regulatory Toxicology and Pharmacology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Improving impact assessments to reduce impacts of deep-sea fisheries on vulnerable marine ecosystems - Laura Kaikkonen; Teresa Amaro; Peter J. Auster; David M. Bailey; James B. Bell; Angelika Brandt; Malcolm R. Clark; Jeffrey C. Drazen; Cherisse Du Preez; Elva Escobar-Briones; Eva Giacomello; Matthew Gianni; et al. (Marine Policy, 2024)

P06-10 NGS-based discovery of circulating microRNA biomarkers of drug-induced pancreatic injury (DIPI) - P. Szatmary; A. Evans; A. Jones; D. Latawiec; W. Cai; A. Kattakayam; C. Goldring; G. Beyer; S. Sirtl; I. Alvarez-Alvarez; W. Bailey; B. Ackermann; et al. (Toxicology Letters, 2024)

Polar science results from Mars Reconnaissance Orbiter: Multiwavelength, multiyear insights - M.E. Landis; P.J. Acharya; N.R. Alsaeed; C. Andres; P. Becerra; W.M. Calvin; E.M. Cangi; S.F.A. Cartwright; M.S. Chaffin; S. Diniega; C.M. Dundas; C.J. Hansen; et al. (Icarus, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Full Hill-type muscle model of the I1/I3 retractor muscle complex in Aplysia californica - Ravesh Sukhnandan; Qianxue Chen; Jiayi Shen; Samantha Pao; Yu Huan; Gregory P. Sutton; Jeffrey P. Gill; Hillel J. Chiel; Victoria A. Webster-Wood (Biological Cybernetics, 2024)
The coordination of complex behavior requires knowledge of both neural dynamics and the mechanics of the periphery. The feeding system of Aplysia californica is an excellent model for investigating questions in soft body systems’ neuromechanics because of its experimental tractability. Prior work has attempted to elucidate the mechanical properties of the periphery by using a Hill-type muscle model to characterize the force generation capabilities of the key protractor muscle responsible for moving Aplysia ’s grasper anteriorly, the I2 muscle. However, the I1/I3 muscle, which is the main driver of retractions of Aplysia ’s grasper, has not been characterized. Because of the importance of the musculature’s properties in generating functional behavior, understanding the properties of muscles like the I1/I3 complex may help to create more realistic simulations of the feeding behavior of Aplysia , which can aid in greater understanding of the neuromechanics of soft-bodied systems. To bridge this gap, in this work, the I1/I3 muscle complex was characterized using force-frequency, length-tension, and force-velocity experiments and showed that a Hill-type model can accurately predict its force-generation properties. Furthermore, the muscle’s peak isometric force and stiffness were found to exceed those of the I2 muscle, and these results were analyzed in the context of prior studies on the I1/I3 complex’s kinematics in vivo.

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

A computational neural model that incorporates both intrinsic dynamics and sensory feedback in the Aplysia feeding network - Yanjun Li; Victoria A. Webster-Wood; Jeffrey P. Gill; Gregory P. Sutton; Hillel J. Chiel; Roger D. Quinn (Biological Cybernetics, 2024)
Studying the nervous system underlying animal motor control can shed light on how animals can adapt flexibly to a changing environment. We focus on the neural basis of feeding control in Aplysia californica . Using the Synthetic Nervous System framework, we developed a model of Aplysia feeding neural circuitry that balances neurophysiological plausibility and computational complexity. The circuitry includes neurons, synapses, and feedback pathways identified in existing literature. We organized the neurons into three layers and five subnetworks according to their functional roles. Simulation results demonstrate that the circuitry model can capture the intrinsic dynamics at neuronal and network levels. When combined with a simplified peripheral biomechanical model, it is sufficient to mediate three animal-like feeding behaviors (biting, swallowing, and rejection). The kinematic, dynamic, and neural responses of the model also share similar features with animal data. These results emphasize the functional roles of sensory feedback during feeding.

Field-scale efficacy of entomopathogenic nematodes to control false codling moth, Thaumatotibia leucotreta (Lepidoptera: Tortricidae), in citrus orchards in South Africa - Sean D. Moore; Ralf-Udo Ehlers; Aruna Manrakhan; Martin Gilbert; Wayne Kirkman; John-Henry Daneel; Jeanne Y. De Waal; Rynhardt Nel; Guy Sutton; Antoinette P. Malan (Crop Protection, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Variability in the phytoplankton response to upwelling across an iron limitation mosaic within the California current system - YuanYu Lin; Olivia Torano; Logan Whitehouse; Emily Pierce; Claire P. Till; Matthew Hurst; Robert Freiberger; Travis Mellett; Maria T. Maldonado; Jian Guo; Mariam Sutton; David Zeitz; et al. (Limnology and Oceanography, 2024)
Coastal upwelling currents such as the California Current System (CCS) comprise some of the most productive biological systems on the planet. Diatoms dominate these upwelling events in part due to their rapid response to nutrient entrainment. In this region, they may also be limited by the micronutrient iron (Fe), an important trace element primarily involved in photosynthesis and nitrogen assimilation. The mechanisms behind how diatoms physiologically acclimate to the different stages of the upwelling conveyor belt cycle remain largely uncharacterized. Here, we explore their physiological and metatranscriptomic response to the upwelling cycle with respect to the Fe limitation mosaic that exists in the CCS. Subsurface, natural plankton assemblages that would potentially seed surface blooms were examined over wide and narrow shelf regions. The initial biomass and physiological state of the phytoplankton community had a large impact on the overall response to simulated upwelling. Following on‐deck incubations under varying Fe physiological states, our results suggest that diatoms quickly dominated the blooms by “frontloading” nitrogen assimilation genes prior to upwelling. However, diatoms subjected to induced Fe limitation exhibited reductions in carbon and nitrogen uptake and decreasing biomass accumulation. Simultaneously, they exhibited a distinct gene expression response which included increased expression of Fe‐starvation induced proteins and decreased expression of nitrogen assimilation and photosynthesis genes. These findings may have significant implications for upwelling events in future oceans, where changes in ocean conditions are projected to amplify the gradient of Fe limitation in coastal upwelling regions.

Degradation of the 2014–2015 Holuhraun vent-proximal edifice in Iceland - S. S. Sutton; J. A. Richardson; P. L. Whelley; S. P. Scheidt; C. W. Hamilton (Bulletin of Volcanology, 2024)
The earliest stages of volcanic vent degradation are rarely measured, leaving a gap in the knowledge that informs landform degradation models of cinder cones and other monogenetic vent structures. We documented the initial degradation of a 500-m-long spatter rampart at the primary vent of the 2014–2015 Holuhraun eruption in northern Iceland with high-resolution topographic change maps derived from terrestrial laser scanning (TLS) and photogrammetric surveys using an unoccupied aircraft system (UAS). Topographic differencing shows a total negative volume change of 42,637 m 3 , and a total positive volume change (basal deposition) of 10,304 m 3 (primarily as deposition at the base of steeply sloping surfaces). Two distinct styles of volume changes were observed on the interior and exterior of the spatter rampart. Material on the interior of the vent was removed from oversteepened slopes by discrete rockfalls, while diffusive processes were qualitatively evident on the exterior slopes. We propose a novel conceptual landform evolution model for spatter ramparts that combines rockfall processes on the interior walls, diffusive gravitational sliding on the exterior slopes, and incorporates cooling contraction and compaction over the entire edifice to describe the observed modes of topographic change during the onset of degradation. Potential hazards at fresh spatter ramparts are rockfalls at high slope areas of the vent interior walls where contacts between spatter clasts are prone to weakening by fumarolic activity, weathering, and settling. To capture such hazards, our data suggest a cadence for monitoring changes yearly for the first few years post-eruption, and at longer intervals thereafter.

MaPPeRTrac: A Massively Parallel, Portable, and Reproducible Tractography Pipeline - Lanya T. Cai; Joseph Moon; Paul B. Camacho; Aaron T. Anderson; Won Jong Chwa; Bradley P. Sutton; Amy J. Markowitz; Eva M. Palacios; Alexis Rodriguez; Geoffrey T. Manley; Shivsundaram Shankar; Peer-Timo Bremer; et al. (Neuroinformatics, 2024)

Control of high-speed jumps in muscle and spring actuated systems: a comparative study of take-off energetics in bush-crickets (Mecopoda elongata) and locusts (Schistocerca gregaria) - Chloe K. Goode; Charlie Woodrow; Shannon L. Harrison; D. Charles Deeming; Gregory P. Sutton (Journal of Comparative Physiology B, 2023)
The Orthoptera are a diverse insect order well known for their locomotive capabilities. To jump, the bush-cricket uses a muscle actuated (MA) system in which leg extension is actuated by contraction of the femoral muscles of the hind legs. In comparison, the locust uses a latch mediated spring actuated (LaMSA) system, in which leg extension is actuated by the recoil of spring-like structure in the femur. The aim of this study was to describe the jumping kinematics of Mecopoda elongata (Tettigoniidae) and compare this to existing data in Schistocerca gregaria (Acrididae), to determine differences in control of rotation during take-off between similarly sized MA and LaMSA jumpers. 269 jumps from 67 individuals of M. elongata with masses from 0.014 g to 3.01 g were recorded with a high-speed camera setup. In M. elongata , linear velocity increased with mass 0.18 and the angular velocity (pitch) decreased with mass −0.13 . In S. gregaria , linear velocity is constant and angular velocity decreases with mass −0.24 . Despite these differences in velocity scaling, the ratio of translational kinetic energy to rotational kinetic energy was similar for both species. On average, the energy distribution of M. elongata was distributed 98.8% to translational kinetic energy and 1.2% to rotational kinetic energy, whilst in S. gregaria it is 98.7% and 1.3%, respectively. This energy distribution was independent of size for both species. Despite having two different jump actuation mechanisms, the ratio of translational and rotational kinetic energy formed during take-off is fixed across these distantly related orthopterans.

Ecotoxicology of mercury concentrations in arctic lamprey (Lethenteron camtschaticum) - Andrew P. Cyr; Katie G. Shink; Sierra Corsetti; Andrew C. Seitz; Trent M. Sutton; J. Andrés López; Matthew J. Wooller; Todd O'Hara (Environmental Research, 2023)

Microplastic ingestion by deep‐pelagic crustaceans and fishes - Ryan P. Bos; Shiye Zhao; Tracey T. Sutton; Tamara M. Frank (Limnology and Oceanography, 2023)
A size‐selective loss of smaller microplastics ( −3 ) and cellophane (density 1.42 g cm −3 ) were mainly consumed. Our data indicate that nonmigratory crustaceans had significantly higher levels of microplastic ingestion than migratory crustaceans at all depths available for comparison. While migratory fishes ingested microplastics at higher frequencies (0.28) than nonmigratory fishes (0.23), the frequency of microplastic ingestion by nonmigratory fishes increased with depth and was highest at depths of 1200–1500 m (0.40). Paired with the data for crustaceans, these observations suggest that plastic ingestion may be higher at deeper depths. Feeding strategy also appeared correlated to microplastic ingestion, as species that rely on gelatinous materials and marine snow for energy had the highest levels of ingestion. Altogether, our data highlight a largely undescribed temporary reservoir and implicate important biological transport pathways for the smaller plastic size fractions in the open ocean.

Vulnerability and resilience of living marine resources to the Deepwater Horizon oil spill: an overview - Steven A. Murawski; Patrick T. Schwing; William F. Patterson; Tracey T. Sutton; Paul A. Montagna; Rosanna J. Milligan; Samantha B. Joye; Len Thomas; Joshua P. Kilborn; Claire B. Paris; Robin Faillettaz; David S. Portnoy; et al. (Frontiers in Marine Science, 2023)
The 2010 Deepwater Horizon (DWH) oil well blowout in the Gulf of Mexico (GoM) was the largest and perhaps most consequential accidental marine oil spill in global history. This paper provides an overview of a Research Topic consisting of four additional papers that: (1) assemble time series data for ecosystem components in regions impacted by the spill, and (2) interpret temporal changes related to the vulnerability of species and ecosystems to DWH and the ensuing resilience to perturbation. Time series abundance data for many taxa pre-date DWH, often by decades, thus allowing an assessment of population- and community-level impacts. We divided the north central GoM into four interconnected “eco-types”: the coastal/nearshore, continental shelf, open-ocean pelagic and deep benthic. Key taxa in each eco-type were evaluated for their vulnerability to the circumstances of the DWH spill based on population overlap with oil, susceptibility to oil contamination, and other factors, as well their imputed resilience to population-level impacts, based on life history metrics, ecology and post-spill trajectories. Each taxon was scored as low, medium, or high for 13 vulnerability attributes and 11 resilience attributes to produce overall vulnerability and resilience scores, which themselves were also categorical (i.e., low, medium, or high). The resulting taxon-specific V-R scores provide important guidance on key species to consider and monitor in the event of future spills similar to DWH. Similar analyses may also guide resource allocation to collect baseline data on highly vulnerable taxa or those with low resilience potential in other ecosystems. For some species, even a decade of observation has been insufficient to document recovery given chronic, long-term exposure to DWH oil remaining in all eco-types and because of impacts to the reproductive output of long-lived species. Due to the ongoing threats of deep-water blowouts, continued surveillance of populations affected by DWH is warranted to document long-term recovery or change in system state. The level of population monitoring in the open-ocean and deep benthic eco-types has historically been low and is inconsistent with the continued migration of the oil industry to the ultra-deep (≥1,500 m) where the majority of leasing, exploration, and production now occurs.

Ecomorphology of a predatory deep-sea fish family: does trophic specialization drive hyperspeciation? - Ryan P. McGonagle; David W. Kerstetter; Danté Fenolio; Tracey T. Sutton (Frontiers in Marine Science, 2023)
Two of the main drivers of speciation among aquatic vertebrates are physical isolation (e.g., lakes and streams) and micro-niche availability (e.g., tropical reefs). In both regards, the mesopelagic domain of the open ocean, Earth’s second largest cumulative ecosystem (behind only the bathypelagic domain), would seem retardant. Ocean circulation makes isolation rare on both contemporary and geological time/space scales, and the lack of substrate precludes stable micro-niches. Paradoxically, some pelagic taxa demonstrate much higher-than-expected species richness on regional scales. A prime example is the dragonfish family Stomiidae, the most speciose family of mesopelagic fishes, owing largely to the subfamily Melanostomiinae (scaleless black dragonfishes), which contributes 222 of the 320 described species. Within genera, species are differentiated almost solely by form of the jugular-positioned, bioluminescent barbel, a structure putatively linked to feeding (via prey luring). The relationship between diversity (both systematic and morphological) and diet within the Melanostomiinae has not been previously examined, primarily due to sample size limitation. Herein, the diet and morphology of 16 species of melanostomiine dragonfishes from the Gulf of Mexico were examined to ascertain whether the diversification in this fish clade is based on prey specialization, as is the case with many other speciose fish families (e.g., Cichlidae). Gut content analysis revealed a rather small spectrum of prey taxa across a wide spectrum of predators, with most species exhibiting piscivory centered on the most regionally abundant lanternfishes (Myctophidae). Lesser numbers of species preyed upon bristlemouths (Gonostomatidae), oceanic basslets (Howellidae), bigscales (Melamphaidae), and other dragonfishes, while three species selected for cephalopod prey. No dragonfish species consumed macrocrustaceans (e.g., decapod shrimps), despite their numerical prevalence as potential prey. Regarding functional morphology, dissimilarity was driven mostly by barbel length, vertical oral gape, and horizontal maxillary oral gape. There were no robust morphological-dietary relationships amongst melanostomiines, with dietary diversity much lower than morphological diversity. These results suggest that other factors, perhaps conspecific recognition and/or sexual selection related to spawning, may be primary drivers of hyperspeciation in the micro-habitat-poor pelagic environment.

Control of high-speed jumps: the rotation and energetics of the locust (Schistocerca gregaria) - C. K. Goode; Gregory P. Sutton (Journal of Comparative Physiology B, 2023)
Locusts ( Schistocerca gregaria ) jump using a latch mediated spring actuated system in the femur-tibia joint of their metathoracic legs. These jumps are exceptionally fast and display angular rotation immediately after take-off. In this study, we focus on the angular velocity, at take-off, of locusts ranging between 0.049 and 1.50 g to determine if and how rotation-rate scales with size. From 263 jumps recorded from 44 individuals, we found that angular velocity scales with mass −0.33 , consistent with a hypothesis of locusts having a constant rotational kinetic energy density. Within the data from each locust, angular velocity increased proportionally with linear velocity, suggesting the two cannot be independently controlled and thus a fixed energy budget is formed at take-off. On average, the energy budget of a jump is distributed 98.7% to translational kinetic energy and gravitational potential energy, and 1.3% to rotational kinetic energy. The percentage of energy devoted to rotation was constant across all sizes of locusts and represents a very small proportion of the energy budget. This analysis suggests that smaller locusts find it harder to jump without body rotation.

GeoSoilEnviroCARS (Sector 13) at the Advanced Photon Source: a comprehensive synchrotron radiation facility for Earth science research at ambient and extreme conditions - S. R. Sutton; M. L. Rivers; S. Chariton; P. J. Eng; A. Lanzirotti; M. Newville; T. Officer; V. B. Prakapenka; Y. J. Ryu; J. E. Stubbs; S. Tkachev; Y. Wang; et al. (Physics and Chemistry of Minerals, 2022)

Stage-dependent niche segregation: insights from a multi-dimensional approach of two sympatric sibling seabirds - Aymeric Fromant; John P. Y. Arnould; Karine Delord; Grace J. Sutton; Alice Carravieri; Paco Bustamante; Colin M. Miskelly; Akiko Kato; Maud Brault-Favrou; Yves Cherel; Charles-André Bost (Oecologia, 2022)
Niche theory predicts that to reduce competition for the same resource, sympatric ecologically similar species should exploit divergent niches and segregate in one or more dimensions. Seasonal variations in environmental conditions and energy requirements can influence the mechanisms and the degree of niche segregation. However, studies have overlooked the multi-dimensional aspect of niche segregation over the whole annual cycle, and key facets of species co-existence still remain ambiguous. The present study provides insights into the niche use and partitioning of two morphologically and ecologically similar seabirds, the common (CDP, Pelecanoides urinatrix ) and the South Georgian diving petrel (SGDP, Pelecanoides georgicus ). Using phenology, at-sea distribution, diving behavior and isotopic data (during the incubation, chick-rearing and non-breeding periods), we show that the degree of partitioning was highly stage-dependent. During the breeding season, the greater niche segregation during chick-rearing than incubation supported the hypothesis that resource partitioning increases during energetically demanding periods. During the post breeding period, while species-specific latitudinal differences were expected (species specific water mass preference), CDP and SGDP also migrated in divergent directions. This segregation in migration area may not be only a response to the selective pressure arising from competition avoidance between sympatric species, but instead, could reflect past evolutionary divergence. Such stage-dependent and context-dependent niche segregation demonstrates the importance of integrative approaches combining techniques from different fields, throughout the entire annual cycle, to better understand the co-existence of ecologically similar species. This is particularly relevant in order to fully understand the short and long-term effects of ongoing environmental changes on species distributions and communities. This work demonstrates the need of integrative multi-dimensional approaches combining concepts and techniques from different fields to understand the mechanism and causal factors of niche segregation.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Systems analysis of miRNA biomarkers to inform drug safety - Amy L. Schofield; Joseph P. Brown; Jack Brown; Ania Wilczynska; Catherine Bell; Warren E. Glaab; Matthias Hackl; Lawrence Howell; Stephen Lee; James W. Dear; Mika Remes; Paul Reeves; et al. (Archives of Toxicology, 2021)
microRNAs (miRNAs or miRs) are short non-coding RNA molecules which have been shown to be dysregulated and released into the extracellular milieu as a result of many drug and non-drug-induced pathologies in different organ systems. Consequently, circulating miRs have been proposed as useful biomarkers of many disease states, including drug-induced tissue injury. miRs have shown potential to support or even replace the existing traditional biomarkers of drug-induced toxicity in terms of sensitivity and specificity, and there is some evidence for their improved diagnostic and prognostic value. However, several pre-analytical and analytical challenges, mainly associated with assay standardization, require solutions before circulating miRs can be successfully translated into the clinic. This review will consider the value and potential for the use of circulating miRs in drug-safety assessment and describe a systems approach to the analysis of the miRNAome in the discovery setting, as well as highlighting standardization issues that at this stage prevent their clinical use as biomarkers. Highlighting these challenges will hopefully drive future research into finding appropriate solutions, and eventually circulating miRs may be translated to the clinic where their undoubted biomarker potential can be used to benefit patients in rapid, easy to use, point-of-care test systems.

State of Satiation Partially Regulates the Dynamics of Vertical Migration - Ryan P. Bos; Tracey T. Sutton; Tamara M. Frank (Frontiers in Marine Science, 2021)
Vertical migrations into shallower waters at night are beneficial for migrators as they reduce predation risk and allow migrators to encounter a higher density of prey. Nevertheless, ocean acoustics data and trawl data have shown that a portion of some vertically migrating populations remain at depth and do not migrate. One hypothesis for this phenomenon is the Hunger-Satiation hypothesis, which in part states that the non-migrating portion of the migrating species-assemblage refrains from migrating if they have full or partially full stomachs from daytime or nocturnal feeding. However, stomach fullness of the non-migrating subpopulation compared to the migrating portion has rarely been studied, due to the difficulty in obtaining sufficient samples. The stomach fullness levels of numerically abundant crustacean and fish species with well-known depth distributions were quantified in the present study. Animals were captured during night trawls from discrete-depth intervals between 0 and 1,500 m. Stomach fullness indices were assigned from 0 to 5 and compared between migratory taxa caught in shallow and deep waters. Data from the crustaceans Acanthephyra purpurea, Gardinerosergia splendens, Plesionika richardi , and Systellaspsis debilis , as well as the fishes Lampanyctus alatus, Lepidophanes guentheri , and Notolychnus valdiviae , provided support for the Hunger-Satiation hypothesis, while data from the crustaceans Gennadas capensis and Gennadas valens and the fish Benthosema suborbitale did not. These findings suggest that stomach vacancy may be just one of several factors regulating the dynamics of vertical migration in those species whose behavioral plasticity suggests daily “choices” in whether or not to vertically migrate.

Fine-scale foraging effort and efficiency of Macaroni penguins is influenced by prey type, patch density and temporal dynamics - G. J. Sutton; C. A. Bost; A. Z. Kouzani; S. D. Adams; K. Mitchell; J. P. Y. Arnould (Marine Biology, 2021)

Trends in Demand of Urban Surface Water Extractions and in Situ Use Functions - E. S. van der Meulen; N. B. Sutton; F. H. M. van de Ven; P. R. van Oel; H. H. M. Rijnaarts (Water Resources Management, 2020)
Scientific literature currently lacks comprehensive understanding of urban surface water use functions. This hampers sound analysis of the demand and potential supply of these functions. This study provides a comprehensive overview of potential use functions, by integrating knowledge from ecosystem services and integrated urban water management fields. Analysis of water-related management plans for Toronto and Amsterdam shows that surface water is currently being used for a variety of functions related to nutrition, energy, water regulation, recreation, symbolic use, transportation and floating buildings. Notably, many use functions involve in situ use, rather than water extractions. Interviewed water managers and spatial planners in both cities expect demand of most use functions to increase by 2040, especially demand for thermal energy extraction, recreation and transportation. Some identified novel demands, such as climate regulation and reuse of waste products from waterway maintenance. Increasing demand is mainly driven by urban growth, climate change and sustainability ambitions. This study found urban surface water uses that are usually not acknowledged in scientific literature on urban water management. This comprehensive overview supports planning, design, and maintenance of urban surface waters, laying the foundation for future research on supply and demand of urban water use functions.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

On the Future of Argo: A Global, Full-Depth, Multi-Disciplinary Array - Dean Roemmich; Matthew H. Alford; Hervé Claustre; Kenneth Johnson; Brian King; James Moum; Peter Oke; W. Brechner Owens; Sylvie Pouliquen; Sarah Purkey; Megan Scanderbeg; Toshio Suga; et al. (Frontiers in Marine Science, 2019)

The Tropical Atlantic Observing System - G. R. Foltz; P. Brandt; I. Richter; B. Rodríguez-Fonseca; F. Hernandez; M. Dengler; R. R. Rodrigues; J. O. Schmidt; L. Yu; N. Lefevre; L. Cotrim Da Cunha; M. J. McPhaden; et al. (Frontiers in Marine Science, 2019)
The tropical Atlantic is home to multiple coupled climate variations covering a wide range of timescales and impacting societally relevant phenomena such as continental rainfall, Atlantic hurricane activity, oceanic biological productivity, and atmospheric circulation in the equatorial Pacific. The tropical Atlantic also connects the southern and northern branches of the Atlantic meridional overturning circulation and receives freshwater input from some of the world’s largest rivers. To address these diverse, unique, and interconnected research challenges, a rich network of ocean observations has developed, building on the backbone of the Prediction and Research Moored Array in the Tropical Atlantic (PIRATA). This network has evolved naturally over time and out of necessity in order to address the most important outstanding scientific questions and to improve predictions of tropical Atlantic severe weather and global climate variability and change. The tropical Atlantic observing system is motivated by goals to understand and better predict phenomena such as tropical Atlantic interannual to decadal variability and climate change; multidecadal variability and its links to the meridional overturning circulation; air-sea fluxes of CO 2 and their implications for the fate of anthropogenic CO 2 ; the Amazon River plume and its interactions with biogeochemistry, vertical mixing, and hurricanes; the highly productive eastern boundary and equatorial upwelling systems; and oceanic oxygen minimum zones, their impacts on biogeochemical cycles and marine ecosystems, and their feedbacks to climate. Past success of the tropical Atlantic observing system is the result of an international commitment to sustained observations and scientific cooperation, a willingness to evolve with changing research and monitoring needs, and a desire to share data openly with the scientific community and operational centers. The observing system must continue to evolve in order to meet an expanding set of research priorities and operational challenges. This paper discusses the tropical Atlantic observing system, including emerging scientific questions that demand sustained ocean observations, the potential for further integration of the observing system, and the requirements for sustaining and enhancing the tropical Atlantic observing system.

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

Physician Communication Practices as a Barrier to Risk-Based HPV Vaccine Uptake Among Men Who Have Sex with Men - Christopher W. Wheldon; Steven K. Sutton; Holly B. Fontenot; Gwendolyn P. Quinn; Anna R. Giuliano; Susan T. Vadaparampil (Journal of Cancer Education, 2018)

Comparison of Health Communication Channels for Reaching Hispanics About Biobanking: a Pilot Trial - Jessica McIntyre; Julio Jiménez; Yonaira M. Rivera; Steven K. Sutton; Gloria Asencio; Eida M. Castro-Figueroa; Clement K. Gwede; Thomas H. Brandon; Susan T. Vadaparampil; Vani N. Simmons; Johanna Corchado; Laura Moreno; et al. (Journal of Cancer Education, 2018)

Spatiotemporal heterogeneity and patterning of developing renal blood vessels - Edward Daniel; D. Berfin Azizoglu; Anne R. Ryan; Tezin A. Walji; Christopher P. Chaney; Gabrielle I. Sutton; Thomas J. Carroll; Denise K. Marciano; Ondine Cleaver (Angiogenesis, 2018)

Energy expenditure of rugby players during a 14-day in-season period, measured using doubly labelled water - Deborah R. Smith; R. F. G. J. King; L. C. Duckworth; L. Sutton; T. Preston; J. P. O’Hara; B. Jones (European Journal of Applied Physiology, 2018)

Identification of the ferredoxin interaction sites on ferredoxin-dependent glutamate synthase from Synechocystis sp. PCC 6803 - Masakazu Hirasawa; Jacaranda Solis; Nanditha Vaidyanathan; Anurag P. Srivastava; R. Max Wynn; Roger B. Sutton; David B. Knaff (Photosynthesis Research, 2017)

Fungal Keratitis Secondary to Trametes betulina: A Case Report and Review of Literature - Joshua S. Hardin; Deanna A. Sutton; Nathan P. Wiederhold; James Mele; Sunali Goyal (Mycopathologia, 2017)

Changing with the times: little penguins exhibit flexibility in foraging behaviour and low behavioural consistency - Elodie C. M. Camprasse; Grace J. Sutton; Maud Berlincourt; John P. Y. Arnould (Marine Biology, 2017)

Decadal predictions with the HiGEM high resolution global coupled climate model: description and basic evaluation - L. C. Shaffrey; D. Hodson; J. Robson; D. P. Stevens; E. Hawkins; I. Polo; I. Stevens; R. T. Sutton; G. Lister; A. Iwi; D. Smith; A. Stephens (Climate Dynamics, 2017)

Ranavirus could facilitate local extinction of rare amphibian species - Julia E. Earl; Jordan C. Chaney; William B. Sutton; Carson E. Lillard; Andrew J. Kouba; Cecilia Langhorne; Jessi Krebs; Rebecca P. Wilkes; Rachel D. Hill; Debra L. Miller; Matthew J. Gray (Oecologia, 2016)

Ustilago echinata: Infection in a Mixed Martial Artist Following an Open Fracture - Ethan Stewart; Sarah Waldman; Deanna A. Sutton; Carmita Sanders; Jonathan Lindner; Hongxin Fan; Nathan P. Wiederhold; George R. Thompson (Mycopathologia, 2016)

An assessment of age and growth of violet cod (Antimora rostrata) in the Ross Sea, Antarctica - Peter L. Horn; Colin P. Sutton (Polar Biology, 2015)

Quantifying alosine prey in the diets of marine piscivores in the Gulf of Maine - S. P. McDermott; N. C. Bransome; S. E. Sutton; B. E. Smith; J. S. Link; T. J. Miller (Journal of Fish Biology, 2015)
The objectives of this work were to quantify the spatial and temporal distribution of the occurrence of anadromous fishes (alewife Alosa pseudoharengus , blueback herring Alosa aestivalis and American shad Alosa sapidissima ) in the stomachs of demersal fishes in coastal waters of the north‐west Atlantic Ocean. Results show that anadromous fishes were detectable and quantifiable in the diets of common marine piscivores for every season sampled. Even though anadromous fishes were not the most abundant prey, they accounted for c. 5–10% of the diet by mass for several marine piscivores. Statistical comparisons of these data with fish diet data from a broad‐scale survey of the north‐west Atlantic Ocean indicate that the frequency of this trophic interaction was significantly higher within spatially and temporally focused sampling areas of this study than in the broad‐scale survey. Odds ratios of anadromous predation were as much as 460 times higher in the targeted sampling as compared with the broad‐scale sampling. Analyses indicate that anadromous prey consumption was more concentrated in the near‐coastal waters compared with consumption of a similar, but more widely distributed species, the Atlantic herring Clupea harengus . In the context of ecosystem‐based fisheries management, the results suggest that even low‐frequency feeding events may be locally important, and should be incorporated into ecosystem models.

Genotyping-by-sequencing based intra-specific genetic map refines a ‘‘QTL-hotspot” region for drought tolerance in chickpea - Deepa Jaganathan; Mahendar Thudi; Sandip Kale; Sarwar Azam; Manish Roorkiwal; Pooran M. Gaur; P B Kavi Kishor; Henry Nguyen; Tim Sutton; Rajeev K. Varshney (Molecular Genetics and Genomics, 2015)

A loop unique to ferredoxin-dependent glutamate synthases is not absolutely essential for ferredoxin-dependent catalytic activity - Jatindra N. Tripathy; Masakazu Hirasawa; R. Bryan Sutton; Afia Dasgupta; Nanditha Vaidyanathan; Masoud Zabet-Moghaddam; Francisco J. Florencio; Anurag P. Srivastava; David B. Knaff (Photosynthesis Research, 2015)

The Grain of Spatially Referenced Economic Cost and Biodiversity Benefit Data and the Effectiveness of a Cost Targeting Strategy - N. J. SUTTON; P. R. ARMSWORTH (Conservation Biology, 2014)
Facing tight resource constraints, conservation organizations must allocate funds available for habitat protection as effectively as possible. Often, they combine spatially referenced economic and biodiversity data to prioritize land for protection. We tested how sensitive these prioritizations could be to differences in the spatial grain of these data by demonstrating how the conclusion of a classic debate in conservation planning between cost and benefit targeting was altered based on the available information. As a case study, we determined parcel‐level acquisition costs and biodiversity benefits of land transactions recently undertaken by a nonprofit conservation organization that seeks to protect forests in the eastern United States. Then, we used hypothetical conservation plans to simulate the types of ex ante priorities that an organization could use to prioritize areas for protection. We found the apparent effectiveness of cost and benefit targeting depended on the spatial grain of the data used when prioritizing parcels based on local species richness. However, when accounting for complementarity, benefit targeting consistently was more efficient than a cost targeting strategy regardless of the spatial grain of the data involved. More pertinently for other studies, we found that combining data collected over different spatial grains inflated the apparent effectiveness of a cost targeting strategy and led to overestimation of the efficiency gain offered by adopting a more integrative return‐on‐investment approach.

Simulation of CO2 and Attribution Analysis at Six European Peatland Sites Using the ECOSSE Model - M. Abdalla; A. Hastings; M. J. Bell; J. U. Smith; M. Richards; M. B. Nilsson; M. Peichl; M. O. Löfvenius; M. Lund; C. Helfter; E. Nemitz; M. A. Sutton; et al. (Water, Air, & Soil Pollution, 2014)

The Bottleneck Effect in Lung Cancer Clinical Trials - Luis E. Gonzalez; Steven K. Sutton; Christie Pratt; Matthew Gilbertson; Scott Antonia; Gwendolyn P. Quinn (Journal of Cancer Education, 2013)

Different plant traits affect two pathways of riparian nitrogen removal in a restored freshwater wetland - A. E. Sutton-Grier; J. P. Wright; C. J. Richardson (Plant and Soil, 2013)

Induction of DREB2A pathway with repression of E2F, jasmonic acid biosynthetic and photosynthesis pathways in cold acclimation-specific freeze-resistant wheat crown - Amrit Karki; David P. Horvath; Fedora Sutton (Functional & Integrative Genomics, 2013)

A verification framework for interannual-to-decadal predictions experiments - L. Goddard; A. Kumar; A. Solomon; D. Smith; G. Boer; P. Gonzalez; V. Kharin; W. Merryfield; C. Deser; S. J. Mason; B. P. Kirtman; R. Msadek; et al. (Climate Dynamics, 2013)

Chemical and antimicrobial treatments change the viscoelastic properties of bacterial biofilms - Warren L. Jones; Michael P. Sutton; Ladean McKittrick; Philip S. Stewart (Biofouling, 2011)

Characterisation of bacteria in ascites—reporting the potential of culture-independent, molecular analysis - G. B. Rogers; L. E. Russell; P. G. Preston; P. Marsh; J. E. Collins; J. Saunders; J. Sutton; D. Fine; K. D. Bruce; M. Wright (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

The evolution of two homologues of the core protein VP6 of epizootic haemorrhagic disease virus (EHDV), which correspond to the geographical origin of the virus - S. J. Anthony; K. E. Darpel; S. Maan; G. Sutton; H. Attoui; P. P. C. Mertens (Virus Genes, 2010)

Myofiber Ellipticity as an Explanation for Transverse Asymmetry of Skeletal Muscle Diffusion MRI In Vivo Signal - Dimitrios C. Karampinos; Kevin F. King; Bradley P. Sutton; John G. Georgiadis (Annals of Biomedical Engineering, 2009)

The inheritance of chemical phenotype in Cannabis sativa L. (IV): cannabinoid-free plants - E. P. M. de Meijer; K. M. Hammond; A. Sutton (Euphytica, 2009)

The mechanics of elevation control in locust jumping - G. P. Sutton; M. Burrows (Journal of Comparative Physiology A, 2008)

Fine mapping and targeted SNP survey using rice-wheat gene colinearity in the region of the Bo1 boron toxicity tolerance locus of bread wheat - Thorsten Schnurbusch; Nicholas C. Collins; Russell F. Eastwood; Tim Sutton; Steven P. Jefferies; Peter Langridge (Theoretical and Applied Genetics, 2007)

The Nightsat mission concept - C. D. Elvidge; P. Cinzano; D. R. Pettit; J. Arvesen; P. Sutton; C. Small; R. Nemani; T. Longcore; C. Rich; J. Safran; J. Weeks; S. Ebener (International Journal of Remote Sensing, 2007)

Focusing of phytodetritus deposition beneath a deep‐ocean front, Chatham Rise, New Zealand - Scott D. Nodder; Gerard C. A. Duineveld; Conrad A. Pilditch; Philip J. Sutton; P. Keith Probert; Marc S. S. Lavaleye; Rob Witbaard; F. Hoe Chang; Julie A. Hall; Ken M. Richardson (Limnology and Oceanography, 2007)
In October 2001, we observed a deep‐ocean phytodetritus deposition event on Chatham Rise beneath the Subtropical Front (STF). The origin of this phytodetritus was probably an extensive phytoplankton bloom that occurred in the STF in the preceding weeks. We assessed the spatial distribution of the deposition event using video images from benthic lander and epibenthic trawl deployments and sediment pigment analyses at six sites on a north—south transect across Chatham Rise. High surficial sediment chlorophyll a concentrations were restricted spatially to the southern flank of Chatham Rise (350–1,200‐m depth) with the highest values centered at ~750‐m water depth (750 S). This southern 750 S site was also the only site where macroscopic phytodetritus was observed, coincident with elevated benthic biomass and sediment community respiration rates. At 750 S, phytodetritus resuspension was observed on video and corroborated by current meter, sediment trap, and optical backscatter measurements, suggesting a threshold erosion current speed for phytodetritus of ~10 cm s −1 , equivalent to a shear velocity of 0.5 cm s −1 and similar to other deep‐ocean studies elsewhere. The restriction of macroscopic phytodetritus deposition to 750 S was related to a zone of current convergence within the STF and lower near‐bed current speeds observed across ~1‐day that promoted deposition. Observations of high benthic biomass and respiration on the southern flank of Chatham Rise suggest that this focusing process is important in fueling the energy demands of benthic communities, in association with the general west‐east advection of organic matter within the STF itself. Such physical focusing of labile organic matter deposition may be an important process in other highly productive frontal systems.

On the climate response of the low-latitude Pacific Ocean to changes in the global freshwater cycle - P. D. Williams; E. Guilyardi; R. T. Sutton; J. M. Gregory; G. Madec (Climate Dynamics, 2006)

Mechanical reconfiguration mediates swallowing and rejection in Aplysia californica - Valerie A. Novakovic; Gregory P. Sutton; David M. Neustadter; Randall D. Beer; Hillel J. Chiel (Journal of Comparative Physiology A, 2006)

Puhimau Thermal Area: A Window into the Upper East Rift Zone of Volcano, Hawaii? - K. A. McGee; A. J. Sutton; T. Elias; M. P. Doukas; T. M. Gerlach (Pure and Applied Geophysics, 2006)

Spatial-Scale Effects on Relative Importance of Physical Habitat Predictors of Stream Health - Emmanuel A. Frimpong; Trent M. Sutton; Bernard A. Engel; Thomas P. Simon (Environmental Management, 2005)

Growth and survival of seedlings of native plants in an impoverished and highly disturbed soil following inoculation with arbuscular mycorrhizal fungi - G. S. Pattinson; K. A. Hammill; B. G. Sutton; P. A. McGee (Mycorrhiza, 2004)

Neural control exploits changing mechanical advantage and context dependence to generate different feeding responses in Aplysia - Gregory P. Sutton; Elizabeth V. Mangan; David M. Neustadter; Randall D. Beer; Patrick E. Crago; Hillel J. Chiel (Biological Cybernetics, 2004)

Passive hinge forces in the feeding apparatus of Aplysia aid retraction during biting but not during swallowing - G. P. Sutton; J. B. Macknin; S. S. Gartman; G. P. Sunny; R. D. Beer; P. E. Crago; D. M. Neustadter; H. J. Chiel (Journal of Comparative Physiology A, 2004)

Absolute geostrophic currents in the East Auckland Current region - P. J. H. Sutton; T. K. Chereskin (New Zealand Journal of Marine and Freshwater Research, 2002)
Absolute geostrophic currents are estimated for the full depth of the water column off the north‐east coast of New Zealand for February 1998. This is achieved by objectively‐mapping subsurface Acoustic Doppler Current Profiler (ADCP) data using horizontal length scales determined from repeat high‐resolution Expendable Bathythermograph (XBT) data and enforcing horizontal non‐divergence. The resulting 2‐dimensional map of velocity at a single depth is used as a level of known motion. Velocities at all other depths are calculated by combining this known motion with the geostrophic shear calculated from hydrographic measurements. The flow field exhibits the expected large‐scale features: the East Auckland Current (EAUC) and the North Cape Eddy. It also indicates that these flows were underestimated by the standard use of a 2000 m level of no motion, i.e., these features penetrate 2000 m. Flows at 2000 m are found to be as large as 30–40 cm/s with a mean of 17 cm/s. This is less than the maximum flows measured by deep current meters, but significantly higher than the mean. Comparisons of the ADCP‐referenced surface flow field with the surface flow field calculated by combining climatology and TOPEX/Poseidon sea‐surface height (SSH) show general qualitative agreement. The two independent flow estimates are similar in the core of the EAUC, with the differences being c. 10 cm/s, whereas the agreement further offshore is not as good.

A case of segmental paternal isodisomy of chromosome 14 - Karen J. Coveler; Sam P. Yang; Reid V. Sutton; Jay M. Milstein; Yuan-Qing Wu; Cami Bois; Linda S. Beischel; John P. Johnson; Lisa G. Shaffer (Human Genetics, 2002)

Biosphere-atmosphere interactions of ammonia with grasslands: Experimental strategy and results from a new European initiative - M.A. Sutton; C. Milford; E. Nemitz; M.R. Theobald; P.W. Hill; D. Fowler; J.K. Schjoerring; M.E. Mattsson; K.H. Nielsen; S. Husted; J.W. Erisman; R. Otjes; et al. (Plant and Soil, 2001)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Glucose, and not sucrose, is transported from wheat to wheat powdery mildew - P. N. Sutton; M. J. Henry; J. L. Hall (Planta, 1999)

Different manifestations of Toxoplasma gondii infection in F344 and LEW rats - Mirjam-Colette Kempf; Marie-France Cesbron-Delauw; Didier Deslee; U. Groß; Thomas Herrmann; P. Sutton (Medical Microbiology and Immunology, 1999)

The clinical phcarmacology of single doses of otilonium bromide in healthy volunteers - J. A. Sutton; S. G. Kilminster; G. P. Mould (European Journal of Clinical Pharmacology, 1997)

Aspects of the hydrodynamics of Beatrix Bay and Pelorus Sound, New Zealand - P. J. H. Sutton; M. G. Hadfield (New Zealand Journal of Marine and Freshwater Research, 1997)
Hydrographic and current meter measurements were performed to determine the important physical processes in Beatrix Bay, an enclosed bay in Pelorus Sound, South Island, New Zealand over a 9‐month period. The water within the bay was highly variable in temperature, salinity, and density, but strongly stratified on all occasions, with the stratification approximating a two‐layer system. The stratification was usually dominated by salinity, but on one occasion, following a period of low rainfall, the stratification was dominated by temperature. A crude estimate of the residence time for the water in Pelorus Sound is calculated from the relaxation towards oceanic salinities during the dry period. The currents measured were largely tidal, and showed evidence of a strong internal tide as a result of the quasi‐two‐layer stratification. The tidal flows were larger than those predicted by a simple model.

Identification and analysis of an alcelaphine herpesvirus 1 (AHV-1) cDNA clone expressing a fusion protein recognized by AHV-1-neutralizing antisera - R. S. Lahijani; S. M. Sutton; R. B. Klieforth; W. P. Heuschele (Archives of Virology, 1995)

Bovine cutaneous papillomas associated with bovine papillomavirus type 5 - N. Bloch; R. H. Sutton; P. B. Spradbrow (Archives of Virology, 1994)